The Social Interaction among students and faculty members in University of Duhok, and its relation with social communication skills and teaching style - Athina Ibrahim; Alan Ibrahim (مجلة الآداب, 2023)
The current study examines and aims to identify the social interaction among students and faculty members in University of Duhok, with its relationship to social communication skills and teaching style. The researcher used a descriptive study, choose the students of University of Duhok as a population of the research with a total (15729) in morning shift with a selection of stratified random sample as consist of (351) in two academic sectors (Humanities and Scientific colleges). The data were collected with a limitation of selecting third stage students in the second semester of the year 2021-2022. To determine the aim of the current research the researcher adopt three measurement scales: (Social Interaction Scale), (Social Communication Skills Scale) and (Teaching Style Scale). Psychometric properties and applied scales were conducted with analyzation data by using (spss) statistical instrument with results of how social communication skills had an impact on social interaction and opposite relation with teaching style. The researcher attempted to verify two hypotheses as results of the research: - The regression model is significant, where the independent variables (social communications skills), (teaching style) affects the dependent variable (social interaction) for the specialization of Humanities. - The regression model is not significant, between the independent variables (social communication skills), (teaching styles) are not affected on the dependent variable (social interaction) for the specialization Sciences.